Sealant for liquid crystal element
Patent Information
- Application Number
- JP2024146468
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-14
AI Technical Summary
【0062】 本発明によれば、低温で熱硬化させた際の低液晶汚染性に優れ、かつ、硬化後の剥離を抑制することができる液晶素子用シール剤を提供することができる。
Smart Images

Figure 2025036296000001 
Figure 2025036296000002 
Figure 2025036296000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant for liquid crystal elements that exhibits excellent low liquid crystal contamination when thermally cured at low temperatures and is capable of suppressing peeling after curing. [Background technology]
[0002] In recent years, as a manufacturing method for liquid crystal elements, from the viewpoint of shortening takt time and optimizing the amount of liquid crystal used, a liquid crystal dropping method using a light-heat curing type sealant containing a curable resin, a photopolymerization initiator, and a heat curing agent, as disclosed in Patent Documents 1 and 2, has been used. In the dropping method, first, a rectangular seal pattern is formed on one of two substrates with electrodes by dispensing. Next, while the sealant is still in an uncured state, tiny droplets of liquid crystal are dropped into the seal frame of the substrate, and the other substrate is placed on top of it in a vacuum, and the seal is temporarily cured by irradiating it with ultraviolet light or other light. After that, it is heated for full curing, and a liquid crystal element is produced. Currently, this dropping method is the mainstream method for manufacturing liquid crystal elements.
[0003] Nowadays, when mobile devices with various liquid crystal panels such as mobile phones and portable game machines are widespread, the miniaturization of devices is the most important issue. One method for miniaturizing devices is to narrow the frame of the liquid crystal display section, for example, by locating the seal section under the black matrix (hereinafter, also referred to as narrow frame design). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-133794 A [Patent Document 2] WO 02 / 092718 Summary of the Invention [Problem to be solved by the invention]
[0005] In a narrow frame design, the sealant is placed directly under the black matrix, so if a dripping method is used, the light irradiated when photo-curing the sealant is blocked, making it difficult for the light to reach the inside of the sealant, resulting in insufficient curing with conventional sealants. When the sealant is not cured sufficiently in this way, there is a problem that uncured sealant components dissolve into the liquid crystal, easily causing liquid crystal contamination. Therefore, studies have been conducted to prevent contamination of liquid crystals by adding a thermal polymerization initiator to the sealant to rapidly heat-cure the parts that are not sufficiently cured by light irradiation. When heating is performed at a low temperature in consideration of damage to liquid crystal elements and environmental activities, if the reaction efficiency of the thermal polymerization initiator is low, it becomes difficult to sufficiently heat-cure the parts that are not sufficiently cured by light irradiation. Therefore, azo initiators with cyano groups are used as thermal polymerization initiators with high reaction efficiency at low temperatures. However, when such a thermal polymerization initiator is used, the obtained cured sealant becomes too hard, and it is not possible to reduce the stress when dividing the multiple cells formed on the mother glass or the stress due to vibration during transportation, which can cause peeling of the substrate.
[0006] An object of the present invention is to provide a sealant for liquid crystal elements which has excellent low liquid crystal contamination properties when thermally cured at low temperatures and which can suppress peeling after curing. [Means for solving the problem]
[0007] Disclosure 1 relates to a sealant for liquid crystal elements, comprising a curable resin, a thermal polymerization initiator, a photopolymerization initiator, and a thermal curing agent, wherein the curable resin comprises a (meth)acrylic compound and an epoxy compound, the (meth)acrylic compound comprises a compound having three or more (meth)acryloyl groups in one molecule, the thermal polymerization initiator is an azo compound having a cyano group and an azo group, at least one of the cyano group and at least one of the azo group are bonded to the same carbon atom, and the carbon atom bonded to the at least one cyano group and the at least one azo group is also bonded to a linear or branched organic group having three or more carbon atoms. The present disclosure 2 relates to a sealant for liquid crystal devices according to the present disclosure 1, wherein the (meth)acrylic compound contains a compound having four or more (meth)acryloyl groups in one molecule. The present disclosure 3 is the sealant for liquid crystal devices according to the present disclosure 1 or 2, wherein the linear or branched organic group having 3 or more carbon atoms contains one or more oxygen atoms. The present disclosure 4 is a sealant for liquid crystal devices according to the present disclosure 1, 2, or 3, wherein the linear or branched organic group having 3 or more carbon atoms contains at least one polar group selected from the group consisting of a carboxy group, an ester bond, and an ether bond. The present disclosure 5 is the sealant for liquid crystal elements according to the present disclosure 1, 2, 3 or 4, wherein a cured product of the sealant for liquid crystal elements has a Martens hardness of 180 MPa or less as measured with a nanoindenter. The present disclosure 6 is the sealant for liquid crystal elements according to the present disclosure 1, 2, 3, 4 or 5, wherein the indentation hardness of a cured product of the sealant for liquid crystal elements, as measured with a nanoindenter, is 30 MPa or less. The present invention will be described in detail below.
[0008] The present inventors have investigated the use of a combination of compounds each having a specific structure as the curable resin and the thermal polymerization initiator in a sealant for liquid crystal elements containing a curable resin, a thermal polymerization initiator, a photopolymerization initiator, and a heat curing agent. As a result, they have found that it is possible to obtain a sealant for liquid crystal elements that is excellent in low liquid crystal contamination when thermally cured at a low temperature and can suppress peeling after curing, and have completed the present invention.
[0009] The sealing agent for liquid crystal elements of the present invention contains a curable resin. The curable resin includes a (meth)acrylic compound and an epoxy compound. In this specification, the term "(meth)acrylic" means acrylic or methacrylic.
[0010] The (meth)acrylic compound includes a compound having three or more (meth)acryloyl groups in one molecule (hereinafter also referred to as "trifunctional or higher (meth)acrylic compound"). By using the trifunctional or higher (meth)acrylic compound in combination with the thermal polymerization initiator according to the present invention described below, the sealing agent for liquid crystal elements of the present invention has excellent low liquid crystal contamination when thermally cured at low temperatures and can suppress peeling after curing. In this specification, the term "(meth)acryloyl" means acryloyl or methacryloyl.
[0011] Examples of the trifunctional or higher (meth)acrylic compound include ethylene oxide-added isocyanuric acid tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. In particular, from the viewpoint of making the resulting sealing agent for liquid crystal elements excellent in low liquid crystal contamination, it is preferable that the above-mentioned (meth)acrylic compound includes a compound having four or more (meth)acryloyl groups in one molecule as the above-mentioned trifunctional or higher functional (meth)acrylic compound. In this specification, the term "(meth)acrylate" means acrylate or methacrylate.
[0012] Among the above tri- or higher functional (meth)acrylic compounds, commercially available ones include, for example, M-315 (manufactured by Toagosei Co., Ltd.) and A-DPH (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0013] The preferred lower limit of the content of the trifunctional or higher (meth)acrylic compound in 100 parts by mass of the curable resin is 5 parts by mass, and the preferred upper limit is 20 parts by mass. When the content of the trifunctional or higher (meth)acrylic compound is 5 parts by mass or more, the resulting sealant for liquid crystal elements has excellent low liquid crystal contamination properties when thermally cured at low temperatures. When the content of the trifunctional or higher (meth)acrylic compound is 20 parts by mass or less, the resulting cured product of the sealant for liquid crystal elements has excellent stress relaxation properties, and peeling can be further suppressed. The more preferred lower limit of the content of the trifunctional or higher (meth)acrylic compound is 7 parts by mass, and the more preferred upper limit is 18 parts by mass, and the even more preferred lower limit is 8 parts by mass, and the even more preferred upper limit is 17 parts by mass.
[0014] From the viewpoints of low liquid crystal contamination, adhesion, moisture resistance, etc., the curable resin preferably contains, as the (meth)acrylic compound, other (meth)acrylic compounds in addition to the trifunctional or higher (meth)acrylic compound. The other (meth)acrylic compound is a compound having one (meth)acryloyl group in one molecule (hereinafter also referred to as a "monofunctional (meth)acrylic compound") or a compound having two (meth)acryloyl groups in one molecule (hereinafter also referred to as a "bifunctional (meth)acrylic compound").
[0015] Examples of the monofunctional (meth)acrylic compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, and the like. (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxy Ethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, glycidyl (meth)acrylate, and the like.
[0016] Examples of the difunctional (meth)acrylic compound include difunctional epoxy (meth)acrylate, difunctional (meth)acrylic acid ester compound, difunctional urethane (meth)acrylate, etc. Among them, difunctional epoxy (meth)acrylate is preferable. In this specification, the epoxy (meth)acrylate refers to a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.
[0017] The difunctional epoxy (meth)acrylate may, for example, be one obtained by reacting a difunctional epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method.
[0018] Examples of the bifunctional epoxy compound that is a raw material for the bifunctional epoxy (meth)acrylate include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, glycidylamine type epoxy compounds, alkyl polyol type epoxy compounds, rubber-modified type epoxy compounds, and glycidyl ester compounds.
[0019] Examples of the bifunctional (meth)acrylic acid ester compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, tert-butyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, and the like.
[0020] The difunctional urethane (meth)acrylate can be obtained, for example, by reacting a difunctional isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.
[0021] Examples of the bifunctional isocyanate compound include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, and tetramethylxylylene diisocyanate.
[0022] Furthermore, as the difunctional isocyanate compound, a chain-extended difunctional isocyanate compound obtained by reacting a polyol with an excess of a difunctional isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0023] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, and mono(meth)acrylates of trihydric alcohols. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin.
[0024] The curable resin may contain, as the other (meth)acrylic compound, a compound having one or more epoxy groups and one or two (meth)acryloyl groups in one molecule. Examples of such compounds include partially (meth)acrylic modified epoxy compounds. The partially (meth)acrylic modified epoxy compound can be obtained, for example, by reacting one of the epoxy groups of the bifunctional epoxy compound with (meth)acrylic acid.
[0025] When the curable resin contains the other (meth)acrylic compound, the content of the other (meth)acrylic compound in 100 parts by mass of the curable resin is preferably 60 parts by mass at the lower limit and 90 parts by mass at the upper limit. By making the content of the other (meth)acrylic compound within this range, the obtained sealant for liquid crystal elements has excellent low liquid crystal contamination, curability, and adhesiveness. The more preferred lower limit of the content of the other (meth)acrylic compound is 65 parts by mass, and the more preferred upper limit is 85 parts by mass.
[0026] Examples of the epoxy compound contained in the curable resin include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber modified type epoxy compounds, and glycidyl ester compounds.
[0027] The epoxy compound content in 100 parts by mass of the curable resin is preferably 5 parts by mass at the lower limit and 30 parts by mass at the upper limit. By making the epoxy compound content within this range, the resulting sealant for liquid crystal elements has excellent low liquid crystal contamination, curability, and adhesiveness. The epoxy compound content is more preferably 10 parts by mass at the lower limit and 20 parts by mass at the upper limit.
[0028] The preferred lower limit of the total content of the curable resin in 100 parts by mass of the sealant for liquid crystal elements of the present invention is 60 parts by mass, and the preferred upper limit is 80 parts by mass. When the total content of the curable resin is within this range, the resulting sealant for liquid crystal elements has better curability and adhesiveness. The more preferred lower limit of the total content of the curable resin is 65 parts by mass, and the more preferred upper limit is 75 parts by mass.
[0029] The sealing material for liquid crystal elements of the present invention contains a thermal polymerization initiator. The thermal polymerization initiator is an azo compound having a cyano group and an azo group. In the azo compound, at least one of the cyano group and at least one of the azo group are bonded to the same carbon atom, and the carbon atom bonded to at least one of the cyano group and at least one of the azo group is also bonded to a linear or branched organic group having 3 or more carbon atoms. Hereinafter, a thermal polymerization initiator consisting of a compound having a carbon atom bonded to all of the cyano group, the azo group, and the linear or branched organic group having 3 or more carbon atoms is also referred to as the "thermal polymerization initiator according to the present invention." By using the thermal polymerization initiator of the present invention in combination with the above-mentioned trifunctional or higher (meth)acrylic compound, the sealing agent for liquid crystal elements of the present invention has excellent low liquid crystal contamination properties when thermally cured at low temperatures, and can suppress peeling after curing. In addition, the thermal polymerization initiator according to the present invention preferably does not have a cyclic skeleton.
[0030] The preferred lower limit of the molecular weight of the thermal polymerization initiator of the present invention is 200, and the preferred upper limit is 300,000. By using the thermal polymerization initiator of the present invention within this range, the resulting sealant for liquid crystal elements is more excellent in the effect of achieving both low liquid crystal contamination when thermally cured at low temperature and stress relaxation after curing. The more preferred lower limit of the molecular weight of the azo compound is 250, and the more preferred upper limit is 100,000. In this specification, the molecular weight is the molecular weight calculated from the structural formula for compounds with specific molecular structure, but may be expressed using the weight average molecular weight for compounds with a wide distribution of polymerization degrees and compounds with unspecified modified sites. In addition, in this specification, the "weight average molecular weight" is a value calculated by measuring using tetrahydrofuran as a solvent by gel permeation chromatography (GPC) and converting it into polystyrene. Examples of columns used when measuring the weight average molecular weight calculated in polystyrene terms by GPC include Shodex LF-804 (manufactured by Showa Denko KK).
[0031] The linear or branched organic group having 3 or more carbon atoms preferably contains one or more oxygen atoms. When the linear or branched organic group having 3 or more carbon atoms contains one or more oxygen atoms, the resulting sealant for liquid crystal elements has excellent low liquid crystal contamination properties. In addition, the linear or branched organic group having 3 or more carbon atoms preferably contains a polar group. When the linear or branched organic group having 3 or more carbon atoms contains a polar group, the resulting sealant for liquid crystal elements has excellent low liquid crystal contamination properties. Among them, it is more preferable that the linear or branched organic group having 3 or more carbon atoms contains at least one polar group selected from the group consisting of a carboxy group, an ester bond, and an ether bond.
[0032] From the viewpoint of further improving the low liquid crystal contamination properties of the resulting sealant for liquid crystal elements, the thermal polymerization initiator of the present invention preferably contains an oxygen atom, and more preferably contains four or more oxygen atoms in one molecule.
[0033] Among them, as the thermal polymerization initiator according to the present invention, a compound represented by the following formula (1) is preferred because the resulting sealing agent for liquid crystal elements has an excellent effect of achieving both low liquid crystal contamination when thermally cured at low temperatures and stress relaxation properties after curing, and at least one selected from the group consisting of 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), and a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) with polyalkylene glycol is more preferred.
[0034] [ka]
[0035] In formula (1), R represents the linear or branched organic group having 3 or more carbon atoms.
[0036] Among the thermal polymerization initiators according to the present invention, commercially available ones include, for example, V-65, V-70, V-501, and VPE-0201 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0037] The content of the thermal polymerization initiator according to the present invention is preferably 0.1 parts by mass at the lower limit and 30 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By using the thermal polymerization initiator according to the present invention within this range, the obtained sealant for liquid crystal elements has an excellent effect of achieving both low liquid crystal contamination when thermally cured at a low temperature and stress relaxation after curing. The more preferable lower limit of the thermal polymerization initiator according to the present invention is 0.5 parts by mass, and the more preferable upper limit is 10 parts by mass.
[0038] The sealing agent for liquid crystal elements of the present invention contains a photopolymerization initiator. Examples of the photopolymerization initiator include a benzophenone compound, an acetophenone compound, an acylphosphine oxide compound, a titanocene compound, an oxime ester compound, a benzoin ether compound, and a thioxanthone compound. Specific examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)- ... -morpholinopropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2-(acetoxyimino)-1-(4-(4-(2-hydroxyethoxy)phenylthio)phenyl)propan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4-dimethylthioxanthen-9-one, and the like.
[0039] The content of the photopolymerization initiator is preferably 0.01 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By setting the content of the photopolymerization initiator within this range, the obtained sealant for liquid crystal elements has better storage stability and photocurability. The more preferred lower limit of the content of the photopolymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0040] The sealing agent for liquid crystal elements of the present invention contains a heat curing agent. Examples of the heat curing agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyhydric phenol compounds, acid anhydrides, etc. Among these, organic acid hydrazides are preferably used.
[0041] Examples of the organic acid hydrazide include sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide. Among the above organic acid hydrazides, commercially available ones include, for example, organic acid hydrazides manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Ltd., and organic acid hydrazides manufactured by Nippon Finechem Co., Ltd. Examples of the organic acid hydrazides available from Otsuka Chemical Co., Ltd. include SDH and ADH. Examples of the organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Inc. include Amicure VDH, Amicure VDH-J, Amicure UDH, and Amicure UDH-J. The organic acid hydrazide manufactured by Japan Finechem Co., Ltd. is, for example, MDH.
[0042] The content of the heat curing agent is preferably 1 part by mass at the lower limit and 50 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By setting the content of the heat curing agent within this range, the resulting sealant for liquid crystal elements has excellent heat curing properties while maintaining storage stability and coatability. The more preferred upper limit of the content of the heat curing agent is 30 parts by mass.
[0043] The sealing material for liquid crystal elements of the present invention preferably contains a filler for the purposes of increasing viscosity, improving adhesion due to a stress dispersion effect, improving the linear expansion coefficient, and improving the moisture resistance of the cured product.
[0044] As the filler, an inorganic filler or an organic filler can be used. Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate. Examples of the organic filler include polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, and acrylic polymer fine particles. The above fillers may be used alone or in combination of two or more kinds.
[0045] The content of the filler is preferably 5 parts by mass at the lower limit and 30 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the filler being within this range, the effect of improving adhesion and the like is excellent without deteriorating the coating property and the like. The more preferable lower limit of the content of the filler is 10 parts by mass, and the more preferable upper limit is 25 parts by mass.
[0046] The sealant for liquid crystal elements of the present invention preferably contains a silane coupling agent. The silane coupling agent mainly serves as an adhesion aid for providing good adhesion between the sealant for liquid crystal elements and a substrate or the like. As the silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, etc. are suitably used.
[0047] The content of the silane coupling agent is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the silane coupling agent being within this range, the effect of improving adhesion while suppressing the occurrence of liquid crystal contamination is excellent. The more preferred lower limit of the content of the silane coupling agent is 0.3 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0048] The sealant for liquid crystal elements of the present invention may contain a light-shielding agent. By containing the light-shielding agent, the sealant for liquid crystal elements of the present invention can be suitably used as a light-shielding sealant.
[0049] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, resin-coated carbon black, etc. Among these, titanium black is preferable.
[0050] The titanium black is a substance that has a higher transmittance for light near the ultraviolet region, particularly light with a wavelength of 370 nm to 450 nm, compared to the average transmittance for light with a wavelength of 300 nm to 800 nm. That is, the titanium black is a light-shielding agent that imparts light-shielding properties to the sealant for liquid crystal elements of the present invention by sufficiently blocking light with wavelengths in the visible light region, while allowing light with wavelengths near the ultraviolet region to pass through. Therefore, by using, as the photopolymerization initiator, one that can initiate a reaction with light of a wavelength (370 nm to 450 nm) at which the transmittance of the titanium black is high, the photocuring property of the sealant for liquid crystal elements of the present invention can be further increased. In addition, the light-shielding agent contained in the sealant for liquid crystal elements of the present invention is preferably a substance with high insulating properties, and titanium black is also suitable as a light-shielding agent with high insulating properties. The titanium black preferably has an optical density (OD value) per 1 μm of 3 or more, more preferably 4 or more. The higher the light blocking ability of the titanium black, the better. There is no particular upper limit to the OD value of the titanium black, but it is usually 5 or less.
[0051] Although the titanium black exhibits sufficient effects even when not surface-treated, it is also possible to use titanium black whose surface has been treated with an organic component such as a coupling agent, or titanium black whose surface has been coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc. Among these, titanium black treated with an organic component is preferred in that it can further improve insulation properties. Furthermore, a liquid crystal display element manufactured using the sealing agent for liquid crystal elements of the present invention, which contains the above-mentioned titanium black as a light-blocking agent, has sufficient light-blocking properties, so that it is possible to realize a liquid crystal display element with no light leakage, high contrast, and excellent image display quality.
[0052] Among the titanium blacks mentioned above, commercially available titanium blacks include, for example, titanium black manufactured by Mitsubishi Materials Corporation and titanium black manufactured by Ako Kasei Co., Ltd. Examples of the titanium black manufactured by Mitsubishi Materials Corporation include 12S, 13M, 13M-C, 13R-N, and 14M-C. An example of the titanium black manufactured by Ako Kasei Co., Ltd. is Tilac D.
[0053] The preferred lower limit of the specific surface area of the titanium black is 13 m 2 / g, the preferred upper limit is 30m 2 / g, and a more preferable lower limit is 15m 2 / g, with a more preferable upper limit of 25m 2 / g. The volume resistivity of the titanium black preferably has a lower limit of 0.5 Ω·cm and a higher limit of 3 Ω·cm, more preferably a lower limit of 1 Ω·cm and a more preferably upper limit of 2.5 Ω·cm.
[0054] The primary particle diameter of the light-shielding agent is not particularly limited as long as it is equal to or smaller than the distance between the substrates of the liquid crystal element, but the preferred lower limit is 1 nm, and the preferred upper limit is 5000 nm. By setting the primary particle diameter of the light-shielding agent within this range, the obtained sealant for liquid crystal elements can have excellent light-shielding properties without deteriorating the coatability, etc. of the sealant. The more preferred lower limit of the primary particle diameter of the light-shielding agent is 5 nm, the more preferred upper limit is 200 nm, the even more preferred lower limit is 10 nm, and the even more preferred upper limit is 100 nm. The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, organic solvent, etc.) using NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0055] The content of the light-shielding agent is preferably 5 parts by mass at the lower limit and 80 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By setting the content of the light-shielding agent within this range, the effect of improving the light-shielding property can be more effectively exhibited without significantly decreasing the adhesiveness, post-curing strength, and drawing property of the resulting sealant for liquid crystal elements. The more preferred lower limit of the content of the light-shielding agent is 10 parts by mass, the more preferred upper limit is 70 parts by mass, the even more preferred lower limit is 30 parts by mass, and the even more preferred upper limit is 60 parts by mass.
[0056] The sealing agent for liquid crystal elements of the present invention may further contain additives such as a reactive diluent, a curing accelerator, a defoaming agent, a leveling agent, and a polymerization inhibitor, if necessary.
[0057] Examples of a method for producing the sealing agent for liquid crystal elements of the present invention include a method of mixing a curable resin, a thermal polymerization initiator, a photopolymerization initiator, a thermal curing agent, and other components such as an inorganic filler and a silane coupling agent using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.
[0058] The preferred upper limit of the Martens hardness of the cured product of the sealant for liquid crystal elements of the present invention measured by a nanoindenter is 180 MPa. When the Martens hardness is 180 MPa or less, the sealant for liquid crystal elements of the present invention has a more excellent stress relaxation property and can further suppress peeling. The more preferred upper limit of the Martens hardness is 150 MPa. Further, there is no particular preferred lower limit for the Martens hardness of the cured product of the sealant for liquid crystal elements of the present invention, as measured with a nanoindenter, but the substantial lower limit is 1 MPa. The Martens hardness is a value calculated from a load-displacement curve obtained when a Berkovich diamond indenter is pressed into the sealant for liquid crystal devices under the conditions of 25°C, maximum pressing load of 100 mN, and pressing depth of 800 nm, in accordance with ISO 14577. 2 The resin is exposed to ultraviolet light for one second, then heated at 80°C for 60 minutes to harden it.
[0059] The preferred upper limit of the indentation hardness (nanoindentation hardness) of the cured product of the sealant for liquid crystal elements of the present invention measured with a nanoindenter is 30 MPa. When the indentation hardness is 30 MPa or less, the sealant for liquid crystal elements of the present invention has a more excellent stress relaxation property and can further suppress peeling. The more preferred upper limit of the indentation hardness is 25 MPa. Further, there is no particular preferred lower limit for the indentation hardness of the cured product of the sealant for liquid crystal elements of the present invention measured with a nanoindenter, but the substantial lower limit is 1 MPa. The indentation hardness is a value calculated from a load-displacement curve obtained when an indentation test is performed using a nanoindenter to indent a Berkovich diamond indenter under the conditions of 25°C, maximum indentation load of 100 mN, and indentation depth of 800 nm, in accordance with ISO 14577. The cured product for measuring the indentation hardness is a sealant for liquid crystal devices with a maximum indentation load of 100 mW / cm. 2 The resin is exposed to ultraviolet light for one second, then heated at 80°C for 60 minutes to harden it.
[0060] Moreover, by blending conductive fine particles with the sealing agent for liquid crystal elements of the present invention, a vertically conductive material can be produced. The conductive fine particles may be metal balls, fine resin particles having a conductive metal layer formed on the surface thereof, etc. Among them, fine resin particles having a conductive metal layer formed on the surface thereof are preferable because the excellent elasticity of the fine resin particles allows conductive connection without damaging a transparent substrate, etc.
[0061] The sealant for liquid crystal elements of the present invention is suitably used as a sealant for liquid crystal cell frames in the production of liquid crystal display elements. As a method for producing the above-mentioned liquid crystal display element using the sealant for liquid crystal elements of the present invention, a liquid crystal dropping method is suitably used, and specifically, for example, a method having the following steps can be mentioned. First, a process is performed in which the sealing agent for liquid crystal elements of the present invention is applied by screen printing, dispenser application, or the like onto the alignment film of one of two transparent substrates having an electrode such as an ITO thin film and an alignment film, thereby forming a frame-shaped seal pattern. Next, a process is performed in which minute droplets of liquid crystal are dropwise applied onto the entire surface within the frame of the seal pattern, and the other transparent substrate is superimposed under vacuum. After that, a liquid crystal display element can be obtained by a process of irradiating the seal pattern portion with light such as ultraviolet light to provisionally cure the seal agent (photocuring process), and a process of heating the provisionally cured seal agent to fully cure it (thermal curing process). Effect of the Invention
[0062] According to the present invention, it is possible to provide a sealant for liquid crystal elements which has excellent low liquid crystal contamination properties when thermally cured at low temperatures and is capable of suppressing peeling after curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0064] (Examples 1 to 12, Comparative Examples 1 to 5) According to the compounding ratios shown in Tables 1 and 2, each material was stirred with a planetary stirrer and then uniformly mixed with a ceramic triple roll to obtain sealants for liquid crystal elements of Examples 1 to 12 and Comparative Examples 1 to 5. Awatori Rentaro (manufactured by Thinky Corporation) was used as the planetary stirrer. In addition, the content of ethylene oxide-added isocyanuric acid triacrylate in ARONIX M-315 in Tables 1 and 2 is 87 to 97% by mass.
[0065] The structures of the thermal polymerization initiators in Tables 1 and 2 are as follows: V-65 (2,2'-azobis(2,4-dimethylvaleronitrile)) is a compound represented by the above formula (1) in which R is a branched organic group having 4 carbon atoms. V-70 (2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile)) is a compound represented by the above formula (1), in which R has 5 carbon atoms and is a branched organic group containing an ether bond. V-501 (4,4'-azobis(4-cyanovaleric acid)) is a compound represented by the above formula (1), in which R is a linear organic group having 3 carbon atoms and containing a carboxy group. VPE-0201 (4,4'-azobis(4-cyanopentanoic acid)·polyethylene glycol condensate) is a compound represented by the above formula (1), in which R is a linear organic group having 5 or more carbon atoms and containing an ester bond and an ether bond. AIBN (2,2'-azobis(isobutyronitrile)) is a compound in which the moiety corresponding to R in the above formula (1) is a linear organic group having one carbon atom. V-59 (2,2'-azobis(2-methylbutyronitrile)) is a compound in which the moiety corresponding to R in the above formula (1) is a linear organic group having two carbon atoms.
[0066] (Martens hardness and indentation hardness of cured product) Each of the obtained sealants for liquid crystal elements was irradiated with a UV irradiator (manufactured by Sen Special Light Sources Co., Ltd., "MB1500T-3") at 100 mW / cm 2The cured product was irradiated with ultraviolet light (wavelength 365 nm) through a 340 nm cut filter for 1 second, and then heated at 80°C for 60 minutes to obtain a cured product with a thickness of 0.3 mm. The cured product was subjected to an indentation test in accordance with ISO14577, in which a Berkovich-type diamond indenter was pressed into the cured product using a nanoindenter (Elionix, "ENT-2100") at 25°C, a maximum indentation load of 100 mN, and an indentation depth of 800 nm. The Martens hardness and indentation hardness (nanoindentation hardness) were calculated from the obtained load-displacement curve. The results are shown in Tables 1 and 2.
[0067] <Evaluation> The sealants for liquid crystal elements obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 and 2.
[0068] (Low liquid crystal contamination when heat cured at low temperatures) One part by mass of silica spacer was added to 100 parts by mass of each of the obtained sealants for liquid crystal elements, and the mixture was uniformly dispersed by a planetary stirrer. The mixture was defoamed to remove bubbles in the sealant for liquid crystal elements, and then filled into a syringe for dispensing, and defoamed again. SI-H055 (manufactured by Sekisui Chemical Co., Ltd.) was used as the silica spacer, and PSY-10E (manufactured by Musashi Engineering Co., Ltd.) was used as the syringe for dispensing. Next, the sealant for liquid crystal elements was applied to a glass substrate so as to draw a frame using a dispenser. SHOTMASTER300 (manufactured by Musashi Engineering Co., Ltd.) was used as the dispenser. Then, minute droplets of FFS liquid crystal were applied dropwise into the frame of the sealant for liquid crystal elements using a liquid crystal dropping device. Another glass substrate was placed on the glass substrate on which the FFS liquid crystal had been applied dropwise, with the sealant for liquid crystal elements interposed between them, and the two glass substrates were bonded together under a reduced pressure of 5 Pa using a vacuum bonding device to obtain a cell. JC-5223XX (manufactured by Chisso Corporation) was used as the FFS liquid crystal. The obtained cell was irradiated with 100 mW / cm2 on the sealant for the liquid crystal element using a UV irradiator (manufactured by Sen Special Light Sources Co., Ltd., "MB1500T-3"). 2After irradiation with ultraviolet light of 340 nm through a 340 nm cut filter for 1 second, the sealant for liquid crystal elements was cured by heating at 80° C. for 60 minutes to prepare a liquid crystal element. The obtained liquid crystal element was checked for alignment disturbance (display unevenness) using a polarizing microscope (Keyence Corporation, "VHX-5000"). Alignment disturbance was judged from color unevenness in the display area, and low liquid crystal contamination was evaluated on a five-level scale from 1 to 5 according to the degree of color unevenness. "1" was given when no color unevenness was observed in the liquid crystal element, and "5" was given when clearly dark color unevenness was observed, with the higher the number indicating greater alignment disturbance. 5 is a level that is unsuitable for practical use.
[0069] (Anti-peeling properties after curing) Using each of the obtained sealants for liquid crystal elements, liquid crystal elements were produced in the same manner as in the above "(Low liquid crystal contamination when thermally cured at low temperature)". The obtained liquid crystal element was vibrated in water for 10 minutes using an ultrasonic cleaner (manufactured by AS ONE Corporation, "VS-10003", 28kH condition). The liquid crystal element after vibration in the ultrasonic cleaner was observed using an optical microscope (manufactured by KEYENCE Corporation, "VHX-5000") to evaluate peeling prevention properties after curing, with "○" indicating no peeling of the substrate and "×" indicating peeling of the substrate.
[0070] [Table 1]
[0071] [Table 2] [Industrial Applicability]
[0072] According to the present invention, it is possible to provide a sealant for liquid crystal elements which has excellent low liquid crystal contamination properties when thermally cured at low temperatures and is capable of suppressing peeling after curing.
Claims
1. The composition contains a curable resin, a thermal polymerization initiator, a photopolymerization initiator, and a thermal curing agent, The curable resin contains a (meth)acrylic compound and an epoxy compound, The (meth)acrylic compound includes a compound having three or more (meth)acryloyl groups in one molecule, The thermal polymerization initiator is an azo compound having a cyano group and an azo group, at least one of the cyano groups and at least one of the azo groups are bonded to the same carbon atom; The carbon atom bonded to at least one of the cyano group and at least one of the azo group is also bonded to a linear or branched organic group having 3 or more carbon atoms. A sealant for liquid crystal elements.
2. 2. The sealant for liquid crystal elements according to claim 1, wherein the (meth)acrylic compound includes a compound having four or more (meth)acryloyl groups in one molecule.
3. 3. The sealant for liquid crystal devices according to claim 1, wherein the linear or branched organic group having 3 or more carbon atoms contains one or more oxygen atoms.
4. 3. The sealant for liquid crystal elements according to claim 1, wherein the linear or branched organic group having 3 or more carbon atoms contains at least one polar group selected from the group consisting of a carboxy group, an ester bond, and an ether bond.
5. 3. The sealant for liquid crystal elements according to claim 1, wherein a cured product of the sealant for liquid crystal elements has a Martens hardness of 180 MPa or less as measured with a nanoindenter.
6. 3. The sealant for liquid crystal elements according to claim 1, wherein a cured product of the sealant for liquid crystal elements has an indentation hardness of 30 MPa or less as measured with a nanoindenter.
Citation Information
Patent Citations
Sealing agent for dropping process of LCD panel
JP2001133794A
Curing resin composition and sealants and end-sealing materials for displays
WO2002092718A1